PENGARUH PEMBELAJARAN MODEL DISCOVERY BERBANTUAN MEDIA SIMULASI PhET TERHADAP HASIL BELAJAR RANAH KOGNITIF TEMA INDAHNYA KEBERAGAMAN DI NEGERIKU KELAS IV SDN GEBANG 3 - Dian Natalia; Nuriman; Agustiningsih (Universitas Negeri Surabaya, 2022)
This research is an experimental study that uses a quasi-experimental design with a non-equivalent control group design research pattern. The purpose of this study was to determine the significant effect of learning the PhET simulation rock discovery model on learning outcomes in the cognitive domain of The Beauty of Diversity Theme in my Country Class IV at SDN Gebang 3. The subjects in this study were fourth grade students at SDN Gebang 3. The implementation of the research in odd semesters. 2022/2023. Data collection techniques used tests and documentation. Data analysis techniques are homogeneity test, normality test, t-test, relative effectiveness test. In data processing using SPSS 25 as a tool. The results of this study indicate that tcount > ttable i.e. 4,200 > 1,674, it can be concluded that there is a significant effect of using the PhET simulation-assisted discovey learning model on learning outcomes in the cognitive domain. 48% yield. This value is included in the moderate effectiveness criteri.